“Síndrome Premenstrual y Habilidades Sociales de las estudiantes de bachillerato de la Unidad Educativa Nazareno, periodo septiembre 2015 - marzo 2016”. - Áldaz Vásquez, Denise Mishel (2016)
This research aims to determine the Premenstrual Syndrome and social skills of students of Bachelor of the “Nazarene educational unit” period September 2015 – 2016 March, knowing that this syndrome is a condition prevalent in women of different ages, whose symptoms produce a considerable decrease in the management of social skills, and overall quality of life. This work is executed with a population consisting of 50 teenagers from high school, with a sample of 40 people, research design is not experimental, and quantitative, the type of research is descriptive, field, transverse, the level of research is exploratory, were used as tools test of Premenstrual syndrome of ret women’s Health Office that he threw as a result that 80 % of the population presents this syndrome, in addition the questionnaire of Miguel Cisneros adapted to learn the social skills he showed us an alteration of 83% in the area of teamwork and finally a questionnaire that allowed to converge the two variables and corroborate information, who gives as a result that the hardest-hit area when adolescent have Premenstrual syndrome is the social with 63%. The analysis of result obtained through data in spreadsheet programs in interphase, allowed us to demonstrate that PMS is eminently presented in adolescents and that this influences the handling of social skills, the area with major alteration being the social area. The research and the results obtained is made recommendations with the purpose that the present study bring and contribute to improve the quality of life.